IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma. Issue 2 (2nd February 2017) - Bergauer, Annika; Sopel, Nina; Kroß, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al.
We analysed the influence of rhinovirus (RV) in nasopharyngeal fluid (NPF) on type I and III interferon (IFN) responses ( e.g. IFN-α and IFN- λ) and their signal transduction, at baseline and during disease exacerbation, in cohorts of pre-school children with and without asthma. At the time of recruitment into the Europe-wide study PreDicta, and during symptoms, NPF was collected and the local RV colonisation was analysed. Peripheral blood mononuclear cells (PBMCs) were challenged in vitro with RV or not. RNA was analysed by quantitative real-time PCR and gene arrays. Serum was analysed with ELISA for IFNs and C-reactive protein. We found that PBMCs from asthmatic children infected in vitro with the RV1b serotype upregulated MYD88, IRF1, STAT1 and STAT2 mRNA, whereas MYD88, IRF1, STAT1 and IRF9 were predominantly induced in control children. Moreover, during symptomatic visits because of disease exacerbation associated with RV detection in NPF, IFN-α production was found increased, while IFN-λ secretion was already induced by RV in asthmatic children at baseline. During asthma exacerbations associated with RV, asthmatic children can induce IFN-α secretion, indicating a hyperactive immune response to repeated respiratory virus infection. Asthma exacerbations associated with rhinovirus in children induce IFN-α and STAT1/STAT2 in PBMCs http://ow.ly/o14r303MW32